DIAGNOSIS OF PULMONARY HYPERTENSION IN SCLERODERMA SYSTEMATICA - A V Volkov; A V Volkov (Современная ревматология)
Pulmonary hypertension (PH) associated with scleroderma systematica (SDS) is a menacing manifestation of this systemic disease of connective tissue, in which a rapid progression results in very poor outcomes. In SDS, PH is more frequently observed with the prolonged disease, circumscribed skin lesion, develops after a long benign course, and is one of the common causes of death. The early stage of PH can be identified by instrumental and not always accessible studies. The stage of clinical manifestations, which is frequently manifested only by dyspnea, requires a differential diagnosis from a wide range of conditions both caused by and concurrent with SDS. The need for differential diagnosis stems from the varying course and prognosis of the disease, as well as treatment policy.